KONVERGENSI MEDIA RADIO REPUBLIK INDONESIA (RRI) SINGARAJA DALAM MEMPERTAHANKAN EKSISTENSI DI ERA DIGITAL - Niluh Wiwik Eka Putri; Ni Putu Arista Dwi Lestariani; I Kadek Abdhi Yasa (Jurnal Nomosleca, 2026)
This study examines the forms of media convergence carried out by Radio Republik Indonesia (RRI) Singaraja to maintain its existence in the digital era. The method used is qualitative phenomenology with data collected through interviews, documentation, observation, and literature review. The results show that RRI Singaraja implements media convergence in four main aspects: technology, industry, social, and regulation. Technological convergence is evident in broadcast digitization and the use of digital platforms such as applications, social media, and YouTube. Industrial convergence is reflected in the use of multiplatforms and cross-sector collaboration. Social convergence is realized through two-way interaction with the community via interactive programs and audience participation. Regulatory convergence is applied through digital guidelines and content regulations in accordance with central standards. Internal factors (organizational culture, human resource quality) and external factors (technology, audience behavior) support the success of the convergence process.